If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -2 = 12 + -52 Reorder the terms: -2 + 2x = 12 + -52 Combine like terms: 12 + -52 = -40 -2 + 2x = -40 Solving -2 + 2x = -40 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 2x = -40 + 2 Combine like terms: -2 + 2 = 0 0 + 2x = -40 + 2 2x = -40 + 2 Combine like terms: -40 + 2 = -38 2x = -38 Divide each side by '2'. x = -19 Simplifying x = -19
| y-(-2)=(3/4)(x-5) | | 25b+20b^3= | | (2x)-(x-4)=5 | | f-(4/1/3)=10 | | 4x+8(x+1)+4=12-4x | | 2x-2(6-4x)=6(x-5)-26 | | f-(41/3)=10 | | 12k+131=3(4k+43) | | 0=-16x^2+40x+2 | | 10(x+2)-2x=2(4x+2)-8 | | 1.2k+2.3=-0.5+7 | | (5u^2+2)-(7u^2-4u+6)= | | 2[3-(6-5r)]-r=-12+3(2+3r) | | (2w^2+3)+(5w^2-4W-6)= | | U/3=12 | | x^2-6x-16/x^2+6x+8 | | (-7u^2+4u-3)+(5u^2+u+6)= | | M/6=8 | | (3t/4) | | (-5v^2+v-3)+(4v^2+6v+2)= | | 32-w=21 | | R-11=20 | | (-5v^2+4-3)+(4v^2+6v+2)= | | P+5=14 | | 19x+9y=300 | | (-2u^2+3u)+(-6u^2-4u+1)= | | N-4=21 | | 4.9090990909= | | 6+p=12 | | y=3/4x-3/2+6/4 | | 6x+2=(x+7)+(x-5) | | 14-x=6 |